Valorizzazione dei centri storici e turismo sostenibile nel bacino del Mediterraneo - Fabio Pollice (Bollettino della Società Geografica Italiana)
Despite its undoubted role as a driver for economic development, tourism in the Mediterranean basin has often compromising effects on the landscape and on the environmental balance of the coastal regions. Also local communities suffer such a negative impact, as they are only marginally affected by the economic benefits deriving from tourism development. Even when they do not remain at the margins of this kind of development processes, historic centers undergo processes of musealization, mystification and disneyfication that are accompanied by the removal of the local population and/or gentrification. The essay moves from the experience gained by the Italian Geographical Society during the Euro-Mediterranean project “Future of Our Past”, in order to propose a model of sustainable development for the historic centers of the Mediterranean area, focusing on the involvement and capability of the local community and enhancing the identity dimension as the distinctive moment of the tourist attractivity.